A tiny lesion arising within Barrett’s esophagus - Francesco Pugliese; Giulia Bonato; Lorenzo Dioscoridi; Marcello Cintolo; Maria Costanza Aquilano; Edoardo Forti; Aurora Giannetti; Angelo Italia; Massimiliano Mutignani (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Pugliese F, Bonato G, Dioscoridi L, et al. A tiny lesion arising within Barrett’s esophagus. Turk J Gastroenterol 2020; 5: 410-2.